Gen Z's Understanding of Internal Controls Dominates QRIS Phishing Prevention - Lukiyana Nurul Izza Kartika; Zaky Machmuddah (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2025)
This study highlights the increasing cases of QRIS phishing targeting Generation Z through social media using various social engineering techniques. The research analyzes the influence of understanding internal controls, risk awareness, and self-efficacy on the effectiveness of QRIS phishing prevention. A quantitative approach was employed with a population of 10,951 active students at Dian Nuswantoro University and a sample of 408 respondents selected through purposive sampling based on their experience conducting QRIS transactions. Data were analyzed using multiple linear regression with SPSS. The results show that understanding internal controls, risk awareness, and self-efficacy have positive and significant effects on QRIS phishing prevention, both simultaneously and partially. Among the three variables, understanding internal controls is the most dominant factor. These findings underscore the importance of strengthening cybersecurity literacy to promote safer digital payment behavior among Generation Z.